2010
DOI: 10.1021/jp910855q
|View full text |Cite
|
Sign up to set email alerts
|

Role of Naphthenic Acids in Stabilizing Water-in-Diluted Model Oil Emulsions

Abstract: The need for alkaline conditions in oil sands processing is, in part, to produce natural surfactants from bitumen. Previous studies have shown that the produced surfactants are primarily carboxylic salts of naphthenic acids with the possibility of sulfonic salts as well. The role of these natural surfactants, particularly those in the naphthenate class, is to provide a physicochemical basis for several subprocesses in bitumen extraction. In this study, it was found that the content of indigenous naphthenic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 26 publications
7
72
0
Order By: Relevance
“…To study the effect of concentration, the number of VO-79 molecules was then increased to 32, corresponding to simulations 5 to 8 in Table 1. These 4 simulations are of bulk concentrations > 28000 ppm (2.8 wt%), which is far above those in our experimental studies as well as those usually employed in other experimental studies 8,30 . where VO-79 are packed on the interface between water and organic solvent.…”
Section: Simulation Systems Simulatedmentioning
confidence: 45%
See 1 more Smart Citation
“…To study the effect of concentration, the number of VO-79 molecules was then increased to 32, corresponding to simulations 5 to 8 in Table 1. These 4 simulations are of bulk concentrations > 28000 ppm (2.8 wt%), which is far above those in our experimental studies as well as those usually employed in other experimental studies 8,30 . where VO-79 are packed on the interface between water and organic solvent.…”
Section: Simulation Systems Simulatedmentioning
confidence: 45%
“…In contrast, experiments reported that IFT can be decreased by asphaltenes at very low bulk concentrations. For instance, for heptol/water interface, IFT reduction was reported by Gao et al 8 (toluene-heptane volume ratio 4:1) at 0.1 wt % of asphaltenes, and by Fan et al 30 (toluene-heptane volume ratio 6:4) at 2~5 g/L of asphaltenes.…”
Section: Introductionmentioning
confidence: 91%
“…[1][2][3][4][5][6][7][8][9][10][11][12]21,22,26,27] However, the lack of molecular structures of asphaltenes that actually stabilize the emulsions hindered the progress in understanding the role of their aggregation and 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 28 interfacial behavior in emulsion stabilization. Asphaltenes do not have well defined amphiphilic structure as in conventional surfactants [48,49] to explain their affinity to adsorb at the oil/water interface.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds include resins, natural surfactants and asphaltenes compounded with fine solids. [1][2][3][4][5][6][7][8][9] As a major stabilizer among these compounds, asphaltenes were found to form 'skin-like' layer at the oil/water interface. This interface prevents coalescence between water droplets by providing mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…The salts within the water and the solids that remain with the bitumen subsequently causes corrosion related problems in downstream unit operations and fouling in unexpected regions of the upgrading facility [7][8][9][10][11][12]. Therefore it is critical that water in oil emulsions found in rag layers are prevented, and that water is removed from the oil well before the upgrading steps.…”
Section: Introductionmentioning
confidence: 99%